Milk yield of crossbred cattle grazing sorghum sudangrass hybrid with concentrate supplementation during dry season - Simili, F. F.; Lima, M. L.P.; Medeiros, M. I.M.; Roma Júnior, L. C.; Paz, C. C.P.; Reis, R. A. [UNESP] (My University, 2018)
The Sorghum Sudangrass Hybrid (SSH) can be used as alternative pasture to be grazed during dry season due to its high tolerance to soil water shortage, lower temperatures and short photoperiod, compared to others perennial grasses. However, there are few reports that used this method as a grazing alternative. The experiment was carried out during three years in order to evaluate the SSH dry pre-grazing forage mass (DFM), stem and leaf proportion and leaf/stem rate (L/S) as well as further analyzing crude protein (CP), neutral detergent fiber (NDF) and milk production of cows receiving or not a supply of 3 Kg of concentrate. There was effect of year and grazing cycle (P < 0.0001) on DFM. The averages were 3041, 1926 and 3482 kg/ha on the 1st, 2 nd and 3rd year, respectively. The CP leaves was higher in 1st and 2nd year with averages of 18.2 and 16.9 % respectively, however, the lowest value was obtained in 3 rd year (P < 0.0001) with average of 12.12%. Milk production of cows that received concentrate supplement was higher (P = 0.0110) than cows did not receive concentrate, milk yields were 17.44 and 15.07 kg/day, respectively. The use of SSH as a pasture during dry season and concentrate supplementation provide an increase of milk production in crossbred cows.
Keywords: Annual grass; Milk composition concentrate; Sorghum bicolor x Sorghum sudanense; Tropical grass